Creating Pipa Performance Exercise Book for Non-Pipa Major First Year Students at Shandong University of Arts, Shandong Province, China - Chen, Wang; Yodwised , Chutasiri; Yongkamol, Yongsit (Journal of Roi Kaensarn Academi, 2024)
This "Pipa Exercise Book" is designed for first-year university students who are not majoring in Pipa. It aims to provide comprehensive guidance, allowing them to grasp the basic techniques and knowledge of Pipa performance. The book covers fundamental aspects of the Pipa, such as its developmental history, structure, as well as techniques for both the left and right hands. Additionally, it includes simple melodies and practice pieces suitable for beginners, along with representative pieces for intermediate learners, intended to help students progressively enhance their performance skills. Through this book, students can systematically learn Pipa performance, establishing a solid foundation for their future studies and development in the field of music. This manual serves as a valuable learning resource for non-Pipa majors, enabling them to better understand and master this ancient and beautiful instrument.